THE WARRIOR TRADITION - Chowder, Ken (PBS, 2019)
It tells the astonishing, heartbreaking, inspiring, and largely-untold story of Native Americans in the United States military. Why would Indian men and women put their lives on the line for the very government that took their homelands? The film relates the stories of Native American warriors from their own points of view, stories of service and pain, of courage and fear.